The Pharmacobiochemical Effects of Ethanol Extract of Justicia secunda Vahl Leaves in Rattus Norvegicus - Onochie AU; Oli AH; Oli AN; Ezeigwe OC; Nwaka AC; Okani CO; Okam PC; Ihekwereme CP; Okoyeh JN (Dove Medical Press, 2020)
Anthony U Onochie,1 Adaobi Helen Oli,1,2 Angus Nnamdi Oli,3 Obiajulu Christian Ezeigwe,4 Andrew C Nwaka,1 Chukwudi O Okani,5 Princeston Chukwuemeka Okam,6 Chibueze P Ihekwereme,7 Jude Nnaemeka Okoyeh8 1Department of Biochemistry Faculty of Natural Sciences, Chukwuemeka Odumegwu Ojukwu University, Uli, Anambra State, Nigeria; 2HIV Lab, HIV Care Unit, Nnamdi Azikiwe University Teaching Hospital, Nnewi, Anambra State, Nigeria; 3Department of Pharmaceutical Microbiology and Biotechnology, Faculty of Pharmaceutical Sciences, Nnamdi Azikiwe University, Agulu, Anambra State, Nigeria; 4Department of Applied Biochemistry, Faculty of Biosciences, Nnamdi Azikiwe University, Awka, Anambra State, Nigeria; 5Department of Histopathology, Faculty of Clinical Medicine, Chukwuemeka Odumegwu Ojukwu University Teaching Hospital Amaku, Awka 420108, Anambra State, Nigeria; 6Department of Pharmacology and Therapeutics, College of Health Sciences, Faculty of Medicine, Nnamdi Azikiwe University, Nnewi, Anambra State, Nigeria; 7Department of Pharmacology and Toxicology, Faculty of Pharmaceutical Sciences, Nnamdi Azikiwe University, Awka, Anambra State, Nigeria; 8Department of Biology and Clinical Laboratory Science, Division of Arts and Sciences, Neumann University, Aston, PA 19014-1298, USACorrespondence: Angus Nnamdi OliDepartment of Pharmaceutical Microbiology and Biotechnology, Faculty of Pharmaceutical Sciences, Agulu, Nnamdi Azikiwe University, Anambra State, NigeriaTel +234 8056306927Email an.oli@unizik.edu.ngPurpose: This study evaluated the biochemical effects of ethanol leaves extract on Wistar rats and also shed light on its constituents and phytonutrients.Methods: The ethanolic extract of J. secunda leaves was prepared using conventional methods. Then, proximate and phytochemical analyses of the extracts were carried out using several methods previously reported in the literatures. The biochemical studies were also carried out as reported in previous literatures.Results: The ethanolic leaves extract contains appreciable quantities of phytonutrients and micronutrients as well as phytochemical constituents. The LD50 of the extract was determined to be 3800mg/kg body weight. There was a dose-dependent elevation of the blood sugar in comparison with the control. There was no significant increase on the bilirubin and liver enzymes levels or on the haematological parameters of the lab animals. The extract significantly elevated the lipid profile (P value < 0.0001), the glomerular filtration rate (increased creatinine and blood urea levels – P value < 0.0001), the serum electrolytes and the animals’ weight. There was a significant decrease in the anion gap (P value < 0.01).Conclusion: The ethanol leaf extract of Justicia secunda has negative cardiac and renal effects on Wistar rats, causing increased lipid profile values, creatinine and blood urea levels in the experimental animals compared with control. The LD50 is below the safety level. Caution should be exercised as the biochemical profiles of cardiac and renal effects do not seem to be promising and the LD50 is below the safety level.Keywords: liver function, kidney function, cardiac function, serum electrolytes, Justicia secunda